1999
DOI: 10.1103/physrevlett.82.2330
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pattern Formation on Ion Bombarded Si(001)

Abstract: Pattern formation on surfaces undergoing low-energy ion bombardment is a common phenomenon. Here, a recently developed in situ spectroscopic light scattering technique was used to monitor periodic ripple evolution on Si(OO1) during Ar+ sputtering. Analysis of the rippling kinetics indicates that under high flux sputtering at low temperatures the concentration of mobile species on the surface is saturated, and, surprisingly, is both temperature and ion flux independent. This is due to an effect of ion collision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
193
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 305 publications
(207 citation statements)
references
References 22 publications
12
193
0
2
Order By: Relevance
“…Lacking more detailed information, it is reasonable to assume a single mobile species which, for simplicity, we will call an "adatom". It has been shown that the assumption of adatom annihilation by direct ion impingement and by diffusion to surface defects or other sinks is consistent with observations of sputterinduced ripple amplification on Si(001) 23,24 .…”
Section: Model For Ion Beam Sculptingsupporting
confidence: 71%
“…Lacking more detailed information, it is reasonable to assume a single mobile species which, for simplicity, we will call an "adatom". It has been shown that the assumption of adatom annihilation by direct ion impingement and by diffusion to surface defects or other sinks is consistent with observations of sputterinduced ripple amplification on Si(001) 23,24 .…”
Section: Model For Ion Beam Sculptingsupporting
confidence: 71%
“…Periodic surface ripples, conical microstructures, whisker-like structures, and pyramidal microstructures have all been observed following high-energy ion-bombardment during sputtering experiments [40,41,42,43,44,45,46,47]. In work that is closely related to our research, conical structures formed after irradiation with nanosecond laser pulses have been observed by several research groups [7,8,10,12,13,14,15,17,48,49,50].…”
Section: Discussionsupporting
confidence: 52%
“…Low energy noble gas ion beams have been applied as an effective tool to modify surface structures and properties on various materials at the nanoscale [7][8][9][12][13][14][15]. Here we present ion beam sculpting results for a variety of noble gas ions and ion beam fluxes to drastically change some of the potentially relevant parameters of the process.…”
Section: Introductionmentioning
confidence: 99%
“…Other methods of nanopore formation are also being actively explored [6]. The physics responsible for the ion beam sculpting process appears to be consistent with an adatom diffusion model [1,7,8]. However, another approach based on the notion of stimulated viscous flow has been advanced to account for the potentially related phenomena of ion beam induced ripple formation [9][10][11], and it must be admitted that the explanation for the ion sculpting phenomena may yet to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%